A consensus statement on child and family health during the COVID-19 pandemic and recommendations for post-pandemic recovery and re-build - Redhead, Caroline A. B.; Silverio, Sergio A.; Payne, Elana; Greenfield, Mari; Barnett, Sara M.; Chiumento, Anna; Holder, Beth; Skirrow, Helen; Torres, Ofelia; Power, Carmen; Weiss, Staci M.; Magee, Laura A.; et al. (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionAs health systems struggled to respond to the catastrophic effects of SARS-CoV-2, infection prevention and control measures significantly impacted on the delivery of non-COVID children's and family health services. The prioritisation of public health measures significantly impacted supportive relationships, revealed their importance for both mental and physical health and well-being. Drawing on findings from an expansive national collaboration, and with the well-being of children and young people in mind, we make recommendations here for post-pandemic recovery and re-build.MethodsThis consensus statement is derived from a cross-disciplinary collaboration of experts. Working together discursively, we have synthesised evidence from collaborative research in child and family health during the COVID-19 pandemic. We have identified and agreed priorities areas for both action and learning, which we present as recommendations for research, healthcare practice, and policy.ResultsThe synthesis led to immediate recommendations grouped around what to retain and what to remove from “pandemic” provision and what to reinstate from pre-pandemic, healthcare provision in these services. Longer-term recommendations for action were also made. Those relevant to children's well-being concern equity and relational healthcare.DiscussionThe documented evidence-base of the effects of the pandemic on children's and family services is growing, providing foundations for the post-pandemic recovery and re-setting of child and family health services and care provision. Recommendations contribute to services better aligning with the values of equity and relational healthcare, whilst providing wider consideration of care and support for children and families in usual vs. extra-ordinary health system shock circumstances.